2021
DOI: 10.1080/21505594.2021.1914448
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of N-acetylmuramyl-L-alanine amidases alters the host immune response to Mycobacterium tuberculosis infection

Abstract: Peptidoglycan (PG), a heteropolysaccharide component of the mycobacterial cell wall can be shed during tuberculosis infection with immunomodulatory consequences. As such, changes in PG structure are expected to have important implications on disease progression and host responses during infection with Mycobacterium tuberculosis. Mycobacterial amidases have important roles in remodeling of PG during cell division and are implicated in susceptibility to antibiotics. However, their role in modulating host immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Infection of bone marrow‐derived macrophages (BMDM) with Δami1 and Δami4 M. tuberculosis ‐mutant strains, genetically defective strains of mycobacterial amidases Ami1 and Ami4, revealed that deletion of one of the two genes resulted in increased secretion of pro‐inflammatory cytokines. Being consistent with that, intranasal infection of mice with the Δami1 M. tuberculosis mutant strains revealed a decrease in specific lymphocyte cell populations in the lungs, a decrease in lung pathology and an elevated cytokine/chemokine response in the lungs 51 …”
Section: Arabinogalactan–peptidoglycan Complexsupporting
confidence: 87%
See 1 more Smart Citation
“…Infection of bone marrow‐derived macrophages (BMDM) with Δami1 and Δami4 M. tuberculosis ‐mutant strains, genetically defective strains of mycobacterial amidases Ami1 and Ami4, revealed that deletion of one of the two genes resulted in increased secretion of pro‐inflammatory cytokines. Being consistent with that, intranasal infection of mice with the Δami1 M. tuberculosis mutant strains revealed a decrease in specific lymphocyte cell populations in the lungs, a decrease in lung pathology and an elevated cytokine/chemokine response in the lungs 51 …”
Section: Arabinogalactan–peptidoglycan Complexsupporting
confidence: 87%
“…Being consistent with that, intranasal infection of mice with the Δami1 M. tuberculosis mutant strains revealed a decrease in specific lymphocyte cell populations in the lungs, a decrease in lung pathology and an elevated cytokine/ chemokine response in the lungs. 51…”
Section: Peptidoglycanmentioning
confidence: 99%
“…All data were reported as mean ± standard deviation (MEAN ± SD). P < 0.05 values were regarded statistically significant 37 …”
Section: Methodsmentioning
confidence: 99%